Meningkatkan kemampuan rawat diri pada anak dengan autism spectrum disorders - Diesmy Humaira Biruny (Universitas Muhammadiyah Malang, 2022)
Autism Spectrum Disorders (ASD) affects all aspects of individual development, including the ability to perform self-care activities, daily living, communication skills and social participation. In this case, the subject experienced a delay in speaking accompanied by symptoms of very poor eye contact, laughing excessively and without reason, speaking a language that was difficult to understand and often grasping the fingers of both hands and moving his feet which resulted in experiencing difficulties in carrying out his daily tasks such as bathing, dressing and eating is included as part of self-care. The assessments used were interviews, observation, Progressive Matrices Test for Children (CPM) and The Childhood Autism Rating Scale (CARS). The intervention given to improve the subject's self-care skills is the provision of positive reinforcement. The results of the intervention that has been given to the subject, behavioral therapy with positive reinforcement techniques are able to improve basic abilities in self-care, especially bathing to washing the face and head, dressing in button-up clothes and eating by not cleaning dirty hands on the clothes worn.